Integrasi Metode Cerita Pendek dalam Pendidikan Kesiapsiagaan Bencana di MTs Waru Sukoharjo - Pratama, Adinda Dwi Septyasarie; Werdani, Kusuma Estu (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2025)
: Disaster mitigation education is essential for school children as a form of early prevention and preparedness enhancement, yet not all schools, including MTs Waru Sukoharjo, provide this training. The objective is to increase the knowledge and preparedness of students at MTs Waru Sukoharjo regarding disasters through educational sessions using the short story book